Buried secrets ebook - Farnsworth, Christopher (Jesse Stone, 2025)
AN INSTANT USA TODAY BESTSELLER Police Chief Jesse Stone investigates the mystery behind a dead body found strewn with photos of murder victims and placed on top of $2 million in cash, before a mob of hit men converge on Paradise. Just another day in Paradise . . .  Chief of Police Jesse Stone is on his way home from a long shift when a call comes in for a welfare check on an elderly resident of the wealthy seaside town of Paradise, Massachusetts. Inside a house packed with junk and trash is a man’s dead body. It’s a sad, lonely end, but nothing criminal . . . until Jesse finds the photos of murder victims strewn around the corpse, on top of a treasure trove of $2 million in cash. Jesse takes on the case and finds a trail leading to an aging mobster who will do whatever it takes to keep the past from coming to light. Before long, Jesse has a price on his head as hit men converge on Paradise to take back the cash and destroy any remaining evidence. But the real danger might be coming from inside his own department. Jesse Stone must unearth the truth buried under the wreckage of a dead man’s life . . . before he winds up in the ground himself.